Development and evaluation of motorcycle immobilizer using radio frequency - Cirineo, Limuel C. (Asia Pacific Higher Education Research Journal (APHERJ), 2015)
This study aimed to develop and evaluate a Motorcycle immobilizer using radio frequency for any kind of motorcycle. Mainly, this device demobilizes the motorcycle in a certain distance after being grabbed and stolen from the parking area. The device, a 27 MHz transmitter-receiver radio frequency that serves as a wireless control to the motorcycle, specifically protects the owner from the heinous criminals and motor jackers throughout the Philippines. Once the transmitter is turned on, the receiver circuit energizes the relays which allow the current from the Circuit Direct Ignition (CDI) to the distributor of the motorcycle. The range of the device reception is up to ten (10) meters, and when the transmitter is out of range, the receiver circuit cuts-off the power of the first relay, but the second relay cuts-off after running for another 21 seconds. The second relay belongs to the off delay circuit in the entire circuitry of the device. The transmitter device has a port for charging the rechargeable battery. Utilizing the experimental method of research to achieve its main objective, the study had data gathered in this research from 251 COT, BIT, BTTE first and second year automotive students officially enrolled in Marikina Polytechnic College (MPC) during the academic year of 2013-2014 and 5 automotive Instructors. These statistical tools treated the data: frequency and ranking, weighted mean, and one factor ANOVA. The study revealed that there is no significant difference between the perceptions of the four groups of respondents as to the design and functionality, usefulness, durability, safety and maintenance of the device. The group of respondents accepted the developed Motorcycle Immobilizer using radio frequency as an anti-thief device for its design and durability, functionality, usefulness and promoting safety and maintenance and security of both the vehicle and the owner as evidenced by its over-all weighted mean of 4.59, verbally interpreted as strongly agree.